Trazendo a interseccionalidade para as RI: Uma análise da atuação da ONU Mulheres no Brasil (2013 – 2021) - Lachini, Maria Celeste Pitanga (2024)
This study aims to promote intersectionality and address intersectional concerns within the field of International Relations. Our analysis is divided into three distinct parts: first, we introduce intersectionality within the theoretical context of IR, exploring the complex interactions between gender and race and their intersections. Next, we examine the implementation of these principles using the United Nations Entity for Gender Equality and the Empowerment of Women (UN Women). We compare UN Women’s guiding documents from 2013 to 2021 with the news published on the official website during the same period. We applied lexical categories in the Content Analysis methodology, supported by GNU Bash software, to identify how intersectionality is addressed in both documents and news. We found that the term "intersectionality" was mentioned only six times in the "Montevideo Strategy" document, revealing a limited approach in the guiding documents. In contrast, in the news, the term was mentioned 22 times starting in 2017. However, we recognize the need to search for compound terms that express the intersections of multiple categories. Notably, the term "race" appeared fewer times than "gender," despite "racism" being mentioned more frequently than "sexism." We conclude that UN Women’s guiding documents still lack a more robust and inclusive approach to intersectionality. On the other hand, the news showed modest growth in covering these issues from 2017 onwards.